Nanostructured Strategies for Melanoma Treatment—Part II: Targeted Topical Delivery of Curcumin via Poloxamer-Based Thermosensitive Hydrogels - Valentina Paganini; Daniela Monti; Patrizia Chetoni; Susi Burgalassi; Andrea Cesari; Fabio Bellina; Silvia Tampucci (Pharmaceuticals)
Background/Objectives: Curcumin (CUR) is a natural compound with notable antitumor properties but faces limitations in topical applications due to poor aqueous solubility, instability, and insufficient skin penetration. To overcome these challenges, a nanomicellar formulation (TPGS30ELP15) was developed to enhance CUR solubility, stability, and skin penetration. This study aimed at evaluating the skin permeation and retention of CUR when delivered through nanomicelles alone or combined with a thermosensitive hydrogel for potential melanoma therapy. Methods: A CUR-loaded nanomicellar formulation containing CUR 5 mM was developed, characterized by particle sizes of 12–25 nm. Skin permeation studies utilized pig ear skin to assess CUR localization using both HPLC quantitative analysis and confocal microscopy. To improve patient comfort and application efficiency, the nanomicellar dispersion was incorporated into a thermosensitive hydrogel based on 16% Kolliphor® P407 and was able to undergo a sol–gel transition at skin temperature (32–36 °C). Formulations were evaluated for physicochemical properties, stability, and CUR distribution within skin layers using in vitro permeation assays. Results: CUR-loaded nanomicelles demonstrated selective localization in the viable epidermis (100–150 µm depth), bypassing the stratum corneum. The addition of the thermosensitive hydrogel enhanced CUR retention and distribution, prolonging contact at the application site and providing a gradual release profile. The hydrogel’s sol–gel transition properties can facilitate ease of use and patient compliance. The combined system effectively delivered CUR to the basal epidermis, a target site for melanoma treatment, achieving therapeutically relevant drug concentrations. Conclusions: The incorporation of CUR-loaded nanomicelles into a thermosensitive hydrogel enhanced the solubility, stability, and targeted delivery of CUR to skin layers. This dual system represents a promising strategy for improving topical drug delivery for melanoma therapy, addressing limitations associated with CUR’s physicochemical properties while ensuring patient-friendly application and gradual drug release.